2008
DOI: 10.1186/1744-8069-4-54
|View full text |Cite
|
Sign up to set email alerts
|

Sumatriptan Inhibits Synaptic Transmission in the Rat Midbrain Periaqueductal Grey

Abstract: Background: There is evidence to suggest that the midbrain periaqueductal grey (PAG) has a role in migraine and the actions of the anti-migraine drug sumatriptan. In the present study we examined the serotonergic modulation of GABAergic and glutamatergic synaptic transmission in rat midbrain PAG slices in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 58 publications
3
21
2
1
Order By: Relevance
“…This was likely to be mediated by a presynaptic mechanism because the increase in evoked IPSCs was associated with a change in their pairedpulse ratio. This differs from and would functionally oppose the 5-HT 1A -and 5-HT 1B/D -induced presynaptic inhibition that we and others have observed previously within the PAG and DRN (Jeong et al 2008;Kishimoto et al 2001;Lemos et al 2006). It can be noted that this 5-HT 2A/C -mediated presynaptic enhancement was observed in the lateral and dorsolateral PAG, the columns in which the 5-HT 2A/C -induced postsynaptic depolarization was most prominent.…”
Section: Postsynaptic Actions Ofcontrasting
confidence: 64%
See 4 more Smart Citations
“…This was likely to be mediated by a presynaptic mechanism because the increase in evoked IPSCs was associated with a change in their pairedpulse ratio. This differs from and would functionally oppose the 5-HT 1A -and 5-HT 1B/D -induced presynaptic inhibition that we and others have observed previously within the PAG and DRN (Jeong et al 2008;Kishimoto et al 2001;Lemos et al 2006). It can be noted that this 5-HT 2A/C -mediated presynaptic enhancement was observed in the lateral and dorsolateral PAG, the columns in which the 5-HT 2A/C -induced postsynaptic depolarization was most prominent.…”
Section: Postsynaptic Actions Ofcontrasting
confidence: 64%
“…We have previously demonstrated that 5-HT inhibits GABAergic synaptic transmission within PAG and that this is mimicked by 5-HT 1A receptor agonists as well as sumatriptan and 5-HT 1B/D receptor agonists (Jeong et al 2008). Given the above finding that 5-HT 2A/C agonists have postsynaptic effects on PAG neurons, we also examined whether DOI modulates GABAergic synaptic transmission.…”
Section: Postsynaptic Actions Ofmentioning
confidence: 95%
See 3 more Smart Citations